If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(8 + -3m) + -5m = 10 (8 * 3 + -3m * 3) + -5m = 10 (24 + -9m) + -5m = 10 Combine like terms: -9m + -5m = -14m 24 + -14m = 10 Solving 24 + -14m = 10 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + -14m = 10 + -24 Combine like terms: 24 + -24 = 0 0 + -14m = 10 + -24 -14m = 10 + -24 Combine like terms: 10 + -24 = -14 -14m = -14 Divide each side by '-14'. m = 1 Simplifying m = 1
| (2x-4)(6x-3)=0 | | 20x-(3x-6)=57 | | x^2+34x-81=0 | | 18x-10=180 | | 2(4z+1)-8=50 | | 3s=210 | | 6x^2+12x-92=-8 | | 42-31= | | (2x-1)(x)=4x-7x+12 | | 8x-1=3x-1 | | 62=30-4(x-4) | | 7y+2y-4= | | 17.5=8y-20 | | 0=r^2-1062.76 | | -4=-27u | | 95=5 | | 62=30(4x-4) | | 2-7(2x+5)=4x-9-x | | -7y-8y=27 | | 4x-2=3x+20 | | -6y-37=26 | | 3w=4.5 | | -6y-3y=26 | | 3x+36=9x-6 | | 2(x-6)+7x=15 | | y=1.50x+18 | | 3t-t=9-t | | 33=4x-3 | | 16-3p=2/3p+5 | | -x^2+9-8=0 | | 3(i-2)=2i+1 | | -20-4n+7n-14=-16 |